1979-1980 Cal Poly Women's Basketball Team (1979)
Back of photo reads: '1979-80 Cal Poly Mustangs. Front Row: Assistant coach Darla Wilson, Jeanine Cardiff, Bobbie Hales, Karen Milstead, Kristin Bryan, head coach Marilyn McNeil, assistant coach Joline Matsunami. Back Row: Erin O'Hagen, Colleen Finney, Laura Buehning, Laurie Sage, Jean Evans, Carolyn Crandall, Joyce Bergner. Not Pictured: Carol Christenson., #18, Page 7'